Congenital toxoplasmosis: potential outcomes and therapeutic challenges - a complex case report of the newborn with treatment-resistant manifestations - Kowalczyk, Emilia; Koziej, Sylwia; Niemczuk, Martyna; Jasiuk, Adrianna; Wiekiera, Mateusz (Journal of Education, Health and Sport, 2024)
Introduction and purpose Toxoplasmosis, a prevalent parasitic infection caused by Toxoplasma gondii, impacts approximately one-third of the global population. Among congenital infections, Congenital Toxoplasmosis (CT) ranks second only to CMV infection in neonates. The severity of fetal and neonatal clinical manifestations depends on factors such as gestational age during infection, parasite load, infectious strain virulence, and maternal immune status. The organogenesis stage in the second trimester is identified as the critical period (10th-24th gestational weeks). Fetal CT may present with ultrasound-detected abnormalities, including intracranial calcifications, microcephaly, hydrocephalus, ascites, hepatosplenomegaly or severe intrauterine growth restriction. Even in the absence of symptoms at birth, CT can lead to long-term consequences such as hydrocephalus, seizures, and cognitive, auditory, and visual impairments. The aim of this study is to present a clinical case of a patient with CT infection complicated by treatment-resistant hydrocephalus and neurological symptoms, including muscle tone disturbances and seizures. Conclusion The significance of screening tests cannot be overstated, as early intervention is crucial to prevent enduring complications. Routine counseling for pregnant women is imperative to raise awareness about Toxoplasma gondii infection, empowering them to adopt necessary preventive measures. Additionally, further research is warranted to assess the efficacy of diverse treatment protocols, the risk of adverse effects, and the effectiveness of emerging therapeutic agents.